An adolescent with disseminated tuberculosis with complicating bronchiectasis - Lestari, Sally Rizkita; Setyoningrum, Retno Asih; Chafid, Arda Pratama Putra; Hapsari, Rika (Edelweiss Applied Science and Technology, 2024)
Disseminated tuberculosis is a potentially fatal condition, and its identification is complicated due to its vague symptoms, together with the limited availability of testing options. Early detection is crucial for prompt diagnosis, as numerous reports indicate favorable responses to first-line anti-tuberculosis medications. Adolescence correlates with an elevated risk of developing tuberculosis, which is often infectious and can serve as a vector for transmission. This particular at-risk group frequently faces significant psychosocial obstacles and distinct issues regarding autonomy and treatment adherence. The case study focuses on an adolescent patient with disseminated tuberculosis complicated by bronchiectasis. It outlines the diagnostic process and treatment plan for a 17-year-old male who came to the pediatric department, primarily complaining of an unproductive cough lasting three weeks. The diagnosis was made based on clinical and radiologic findings. A considerable number of individuals may develop bronchiectasis as a complication of the illness, particularly in cases of pulmonary tuberculosis. These illnesses impose a substantial burden globally regarding morbidity, death, and financial impact on the affected populations. Both tuberculosis and bronchiectasis continue to be major public health concerns in developed and developing nations alike.